FOLLOW-UP AND PROGRESSION OF HEMOPERITONEUM DEVELOPED IN A TYPE 3 VON WILLEBRAND PATIENT SECONDARY TO THE HEMORRHAGIC RUPTURE OF CORPUS LUTEUM - Akarsu, S.; Atilgan, R.; Altun, M. (Ferrata Storti Foundation, 2013)
[Abstract Not Available]